Defiance of stable lysogeny reveals hidden infection dynamics of phage Lambda - Kevin Broux; Leonard E. Bäcker; Dries Oome; Flo Baert; Jef Vandenborre; Seppe Schoeters; Ninh Hieu Luan Tran; Kenneth Simoens; Steffen Waldherr; Kristel Bernaerts; Abram Aertsen (Proceedings of the National Academy of Sciences, 2026)
Stable prophage establishment is considered a quintessential response of temperate phages when faced with host cell depletion. Scrutinizing this behavior in model phage λ, however, revealed that many λ-chromosomes avoid stable integration in the host chromosome, and rather assume a nonintegrated prophage-like (or pλ) state inside the cell that keeps expressing CI-based immunity and becomes asymmetrically segregated. This creates a heterogeneous population of host cells that are either i) immune by stably carrying an integrated λ prophage, ii) immune by carrying a pλ-episome, or iii) λ-free and transiently immune by segregating from a pλ-carrier. Superinfection of these immune cells drains the number of λ-virions and creates more pλ-episomes that prolong the immunity and expansion of the λ-free subpopulation. The subsequent decline in λ-virions causes cytoplasmically inherited CI-levels in λ-free siblings to dilute out, poising them for renewed lytic consumption by λ. These overlooked pλ-dynamics attenuate the importance of prophage establishment and permit a more productive phage–host coexistence.